The creative capital of cities : interactive knowledge creation and the urbanization economies of innovation - Krätke, Stefan, 1952- (Studies in urban and social change, 2011)
"The Creative Capital of Cities challenges the new urban growth concepts of creative industries from a critical urban theory perspective. The author presents both technological creativity in knowledge-intensive industries and artistical creativity in the cultural economy sector in the analysis of the 'creative capital of cities'. Krätke develops a transdisciplinary approach to the analysis of creativity and knowledge generation in an urban context by combining perspectives of economic geography, regional research, and socio-cultural urban studies. Providing deep insights backed up by rigorous empirical analysis, The Creative Capital of Cities reveals the complex relational dimensions of creativity while offering an alternate path to the assessment of urban economic success"--Vydavatelská anotace